2020
DOI: 10.1111/jfbc.13513
|View full text |Cite
|
Sign up to set email alerts
|

Salacia chinensisexerts its antidiabetic effect by modulating glucose‐regulated proteins and transcription factors in high‐fat diet fed‐streptozotocin‐induced type 2 diabetic rats

Abstract: Diabetes mellitus (DM) is a disease characterized by abnormal carbohydrate metabolism, associated with abnormal insulin secretion from β-pancreatic cells (type 1 DM) or its poor action on target cells (type 2 DM) (Petersmann et al., 2018). It is projected that the number of people with DM globally would become 552 million by 2030, thus, representing a public health problem (Whiting et al., 2011). It has been reported that a sedentary lifestyle, genetic predisposition, and obesity increase the risk of developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Previously many studies have reported that antioxidant capacity was reduced by type 2 diabetes (Erten et al, 2020 ; Goboza et al, 2019 ; Kheiripour et al, 2019 ; Sahin et al, 2019 ). Also, it is well‐known that MDA, a lipid peroxidation marker, levels significantly increase in serum (Sahin et al, 2019 ) and liver (Kheiripour et al, 2019 ) due to lipotoxicity, low‐grade inflammation, and oxidative stress in HFD/STZ‐induced type 2 diabetes (Singh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously many studies have reported that antioxidant capacity was reduced by type 2 diabetes (Erten et al, 2020 ; Goboza et al, 2019 ; Kheiripour et al, 2019 ; Sahin et al, 2019 ). Also, it is well‐known that MDA, a lipid peroxidation marker, levels significantly increase in serum (Sahin et al, 2019 ) and liver (Kheiripour et al, 2019 ) due to lipotoxicity, low‐grade inflammation, and oxidative stress in HFD/STZ‐induced type 2 diabetes (Singh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive fat intake elevated serum and liver FFA may promote inflammatory hepatic damage and insulin resistance (Ma et al, 2018 ), leading to the deterioration of glucose metabolism and subsequent hyperglycemia, hyperinsulinemia, and dyslipidemia (Sahin et al, 2019 ). Also, STZ targets the insulin‐producing the β‐cells and may break down tissue proteins, resulting in body weight loss (Erten et al, 2020 ). Therefore, this study confirmed that with body weight loss, serum triglyceride, cholesterol, FFA, insulin, and glucose levels were tightly associated with type 2 diabetes and significantly increased in HFD/STZ rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, overnight-fasted animals were administered intraperitoneally (i.p.) with a single dose of 40 mg/kg STZ, prepared in a 0.1 M cold citrate buffer (pH 4.5), and monitored for 3 days as previously described [ 67 , 68 , 69 ]. A blood glucose level of > 250 mg/dL was confirmed as a state of hyperglycemia.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, NRF2 activity can be modified by daily consumption of specific food and phytochemicals. Most of these micronutrients/compounds are contained in plant-based food such as kaempferol (a polyphenol found in some fruits and vegetables), niga-ichigoside (a triterpenoid saponin from rosacea), salacia chinensis extracts (a climbing plant that contains triterpenes, phenolic compounds, and glycosides), hydroxytyrosol (the main phenolic compound in olives), curcumin, rebaudioside (a sweetener from Stevia rebaudiana), chicoric acid, and omega 3 and polyunsaturated fatty acids [ 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ]. In addition, NFE2L2 gene expression can be upregulated by fibre-enriched diets [ 179 ].…”
Section: Nrf2 and Brain (Dys)functionsmentioning
confidence: 99%